2022
DOI: 10.1177/19417381221093557
|View full text |Cite
|
Sign up to set email alerts
|

Is Workload Associated With Hamstring and Calf Strains in Professional Baseball Players? An Analysis of Days of Rest, Innings Fielded, and Plate Appearances

Abstract: Background: The influence of player workload on hamstring and calf injuries in professional baseball players remains unknown. Hypothesis: Increased workload would significantly increase hamstring and calf strain injury risk. Study Design: Case-control. Level of Evidence: Level 3. Methods: All professional baseball players who sustained a hamstring or calf injury between 2011 and 2017 were identified using the Major League Baseball (MLB) Health and Injury Tracking System (HITS). A separate player usage dataset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(25 reference statements)
0
2
0
Order By: Relevance
“… 22 Multiple subsequent studies have confirmed the relationship between workload and arm pain. 6 , 7 , 12 , 20 , 25 , 26 , 35 This relationship may be driven by changes in mechanics with fatigue. 9 , 14 , 28 However, although there is a clear relationship between pain and workload, not all studies have confirmed a relationship between injury and workload.…”
mentioning
confidence: 99%
“… 22 Multiple subsequent studies have confirmed the relationship between workload and arm pain. 6 , 7 , 12 , 20 , 25 , 26 , 35 This relationship may be driven by changes in mechanics with fatigue. 9 , 14 , 28 However, although there is a clear relationship between pain and workload, not all studies have confirmed a relationship between injury and workload.…”
mentioning
confidence: 99%
“…3 Previous research involving workload demands of position players within professional baseball has been limited. Only one study to date has explored the relationship between lower limb soft tissue injuries (hamstring and calf strains) and workload among position players at the professional level, 7 during which they showed a link between injury and workload factors such as fewer days rest, increased innings, and increased plate appearances. Workload (defined as games played, at-bats, plate appearances, and innings) was not associated with changes in hip range of motion throughout the course of a season of professional baseball.…”
mentioning
confidence: 99%